Maize drought protection by Azospirillum argentinense Az19 requires bacterial trehalose accumulation - Garcia, Julia Elena; Pagnussat, Luciana Anabella; Amenta, Melina B.; Casanovas, E. Mabel; Diaz, Pablo R.; Labarthe, María Mercedes; Martino, María V.; Groppa, María Daniela; Creus, Cecilia Mónica; Maroniche, Guillermo Andrés (Springer, 2025)
Azospirillum argentinense Az19 is an osmotolerant plant growth-promoting bacterium that protects maize plants from drought. In this work, we explored the role of trehalose in the superior performance of Az19 under stress. The trehalase-coding gene treF was constitutively expressed in Az19 through a miniTn7 system. The resulting recombinant strain, Az19F, did not accumulate trehalose, was affected in its capacity to cope with salt-, osmotic-, and UV-stress, and showed higher reactive oxygen species levels. Physiological alterations were also observed under normal conditions, such as increased growth in biofilms, higher motility, and decreased auxin secretion. Even so, the capacity of Az19F to colonize maize roots was not affected, either under normal or drought conditions. When inoculated in maize, both Az19 and Az19F strains promoted plant growth similarly under normal irrigation. However, unlike Az19, the trehalose-deficient strain Az19F could not improve the height, aerial fresh weight, or relative water content of maize plants under drought. Notably, Az19F triggered an exacerbated oxidative response in the plants, resulting in higher levels of antioxidant and phenolic compounds. We conclude that the role of trehalose metabolism in A. argentinense Az19 transcends stress tolerance, being also important for normal bacterial physiology and its plant growth-promoting activity under drought.